SAT0185 Wnt5a Promotes Fibroblast Activation and Tissue Fibrosis by ROR2/ RYK Dependent Activation of PCP-Signaling. (15th July 2016) - Chen, C.-W.; Lin, N.-Y.; Zhang, Y.; Huang, J.; Palumbo-Zerr, K.; Schambony, A.; Beyer, C.; Schett, G.; Distler, J.H.
Abstract : Background: Canonical Wnt/beta-catenin signaling has been identified as a core pathway of fibrosis in SSc. However, the role of non-canonical Wnt signaling has not yet been investigated. A subset of Wnt proteins such as Wnt5a can bind to different cell surface receptors and activate non-canonical Wnt pathways which are independent of beta-catenin pathway. Objectives: In this study we aimed to characterize the role of non-canonical Wnt signaling in fibrotic diseases and find out the major target receptor for further therapeutic antibody generation. Methods: The expression of non-canonical Wnt ligands was analyzed by qPCR, IF and Western blot in patients with SSc, IPF and healthy controls as well as in experimental fibrosis. The effect of fibroblast-specific (col1a2; CreER) as ubiquitous (ubiquitin; CreER) knockout of Wnt5a was evaluated in bleomycin-induced fibrosis and in experimental cGvHD. Wnt5a was overexpressed in 3D human skin culture systems and in the skin and lungs of mice using adeno-associated vectors. Wnt5a-induced signaling pathways were analyzed in vitro and in vivo using small molecule inhibitors, siRNA mediated knockdown, Western blots and reporter assays. Results: The mRNA and protein levels of Wnt5a, but not other non-canonical Wnt ligands, were increased in skin and lungs of patients with SSc and IPF as compared to healthy volunteers. Wnt5a was also upregulated in murine models of fibrosis. Co-staining with cell-type specific markers identified fibroblasts as a major cellular source of Wnt5a in fibrotic diseases. Wnt5a induced myofibroblast differentiation and collagen release in vitro and induced pulmonary and dermal fibrosis in vivo . In contrast, inducible fibroblast-specific knockout of Wnt5a ameliorated bleomycin-induced fibrosis and experimental cGvHD. The effects of fibroblast-specific knockout were comparable to those in mice with inducible ubiquitous knockout. The pro-fibrotic effects of Wnt5a were independent of Wnt/beta-catenin and Wnt/Calcium signaling, but were mediated by Wnt/PCP signaling via binding with Ror2 and Ryk receptors and subsequent phosphorylated JNK and cJun. Consistently, pharmacologic or genetic inactivation of JNK or cJun abrogated the pro-fibrotic effects of Wnt5a in vitro and in vivo . Co-incubation with neutralizing antibodies against TGFbeta and inhibitors of TGFbeta receptors demonstrated that the profibrotic effects of Wnt5a were partially mediated by rapid activation of latent TGFbeta with subsequent activation of classical downstream pathways such as Smad3. Conclusions: We characterize Wnt5a as a novel mediator of fibroblast activation in fibrotic diseases. Wnt5a is upregulated in SSc and IPF and induces fibroblast activation and tissue fibrosis. The pro-fibrotic effects of Wnt5a are independent of canonical Wnt signaling and Wnt/Calcium signaling, but are mediated by PCP signaling via binding with Ror2 and Ryk receptor and JNK/cJun activation and by activation of latent TGFbeta. Disclosure of Interest: None declared